Analysis of the ASEAN master plan on rural development of inclusive green villages in Tanjung Lanjut Village - Rts. Nur Rahmawati; Faradina Zevaya; Rohayatul Husna; Thalia Anggraini; Yusi Amelinda (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2026)
This research examines the prospects of rural level development according to the ASEAN Framework by proposing the concept of inclusive green villages to tackle challenges such as poverty and environmental degradation. We use Tanjung Lanjut Village in Muaro Jambi as our main case study in highlighting the importance of active community participation in both the planning and implementation of development projects. Furthermore, sustainable investment plays a critical role in achieving significant progress. This study uses qualitative research methodology with data collected through interviews, focus group discussions (FGDs) involving community representatives, and surveys. The analysis is conducted with NVivo software. The findings further reveal that limited access to finance, technological adoption, and weak local institutional capacity are major barriers in achieving inclusive and green rural development. Proposed strategies to address these challenges include improving communication and coordination among stakeholders, strengthening infrastructure, providing capacity-building training for the local community, and facilitating access to sustainable financing. This study emphasize the importance of collaborative efforts among stakeholders, such as governments, communities, and investors to achieve inclusive and environmentally friendly development of rural areas which is in line with Sustainable Development Goals (SDGs) within the ASEAN regional context. The conclusion of this study indicates that rural development, particularly in the ASEAN region, holds significant potential to contribute to the SDGs. By adopting the concept of green, inclusive villages, and focusing on sustainable investment, active community participation, and capacity building, rural areas can achieve inclusive economic growth while addressing environmental challenges. However, the success of such development is dependent on effective resource management, improved living standards, and strong governance practices.